2022
DOI: 10.1093/aje/kwab290
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic and Geographic Trends in Combined Stimulant/Opioid Overdoses, 2007–2019

Abstract: In the United States, combined stimulant/opioid overdose mortality has risen dramatically over the last decade. These increases may particularly affect non-Hispanic Black and Hispanic populations. We used death certificate data from the US National Center for Health Statistics (2007–2019) to compare state-level trends in overdose mortality due to opioids in combination with 1) cocaine and 2) methamphetamine and other stimulants (MOS) across racial/ethnic groups (non-Hispanic White, non-Hispanic Black, Hispanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 58 publications
0
41
0
Order By: Relevance
“…While polysubstance fatal overdose rates are outside the scope of this paper, such deaths are increasingly common and warrant future research to identify potential interventions. 2 Patterns of polysubstance fatal overdoses are complex and have changed over time and across racial and ethnic groups and our stratified analyses cannot convey the full complexity of these changing patterns (Supplemental Figure S14). Consistent with previous research, we removed COVID-19 deaths from our estimation of excess mortality; however, it is likely that people who use drugs are at higher risk of contracting and dying from COVID-19 and this competing risk may bias our estimates of excess drug-related mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While polysubstance fatal overdose rates are outside the scope of this paper, such deaths are increasingly common and warrant future research to identify potential interventions. 2 Patterns of polysubstance fatal overdoses are complex and have changed over time and across racial and ethnic groups and our stratified analyses cannot convey the full complexity of these changing patterns (Supplemental Figure S14). Consistent with previous research, we removed COVID-19 deaths from our estimation of excess mortality; however, it is likely that people who use drugs are at higher risk of contracting and dying from COVID-19 and this competing risk may bias our estimates of excess drug-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the US topped 100,000 drug-related deaths for the first time. 1 There is substantial variation in opioid-related mortality across geographic region and type of opioid, with recent increases in synthetic opioid deaths and cooccurrence of opioids with other illicit substances 2 in the total population and recent increases in opioid-related mortality in the non-Hispanic Black and non-Hispanic American Indian or Alaska Native populations. 3 , 4 , 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…According to recent estimates, there are ~18 million cocaine users worldwide, with the highest rates in the US (2.1%). A recent study identified that areas dense in black and Hispanic racial/ethnic groups had a 575% increase in cocaine and opioid mortality rate compared to a 184% increase across white groups ( 8 ). From 2015 until 2019, psychostimulants' overdose among US adults, largely methamphetamine, increased by 180% (from 5526 to 15,489 overdosage estimates) ( 20 ).…”
Section: Opioids and Stimulants Trends In General And During Covid-19mentioning
confidence: 99%
“…It's unclear if the link between these drugs and overdose mortality is due to drug interactions or if drug users overdose on heroin to reduce their stimulated “highs” ( 7 ). Our personal experience at a methadone clinic in rural Vermont, as well as current literature suggests that individuals who use concurrent opioids and stimulants believe stimulants are safer, combining stimulants and opioids to offset the negative effects of opioids, such as withdrawal symptoms, limiting opioid use, finding cheaper substitutes for heroin, relieving fatigue, lethargy, and some combining to enhance a “high” ( 6 , 8 ). However, in many cases, fentanyl is mixed with cocaine or methamphetamine without the user's knowledge, and a person with no tolerance to opioids may suffer a fatal overdose ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…11,[13][14][15] Moreover, non-Hispanic Blacks and American Indians and Alaska Natives (AIAN) experienced the highest increases in the drug overdose mortality rates in 2019 and 2020, 16 while non-Hispanic Blacks experienced much higher increase of the mortality rates due to stimulants and opioids co-ingestion compared to non-Hispanic Whites. 17 It has also been reported that people with lower income, living in non-metro urbanized regions, or uninsured are more likely to suffer from SUD. 18 Multiple disparities may co-exist, and exacerbate the likelihood of SU/SUD.…”
Section: Introductionmentioning
confidence: 99%